Transanal total mesorectal excision port-assisted perineal hernia repair: A case report - Peng, Xudong; Ge, Yinggang; Zhang, Jianwen; Wei, Zhengqiang; Zhang, Hongyu (Frontiers in Oncology, 2022)
Perineal hernia after abdominoperineal resection (APR) is a troublesome problem, and severe cases require surgical treatment. However, perineal hernia repair is challenging, especially when combined with intestinal adhesions. The difficulty of the operation lies in performing adhesiolysis and mesh placement under poor visibility. While there are traditional, laparoscopic and even robotic methods of performing this procedure, no easy and minimally-invasive approach has been reported. Here, we report the case of a patient with perineal hernia, who underwent transanal total mesorectal excision (TaTME) port-assisted laparoscopic perineal hernia repair. The operation was successful, the postoperative recovery was uneventful, the patient’s symptoms improved significantly, and no recurrence was found during the 4-month follow-up. The availability and safety of TaTME port-assisted perineal hernia repair provide a promising approach for hernia repair. Compared with traditional perineal or laparoscopic abdominal approaches, this procedure is less invasive and results in a better field of vision.